2020
DOI: 10.3389/fpsyg.2020.01985
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of the Personal and Professional Threat Perception of Olympic Athletes in the Actual COVID-19 Crisis

Abstract: The COVID-19 pandemic is now a major global health issue, affecting world population and high-performance athlete too. The aim of the present research was to analyze the effect of psychological profile, academic schedule, and gender in the perception of personal and professional threat of Olympic and Paralympic athletes facing the 2021 Tokyo Olympiad in the actual COVID-19 crisis. We analyzed in 136 Olympic (26.4 ± 6.2 years) and 39 Paralympic athletes (31.8 ± 9.3 years) academic and sport variables, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
117
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 31 publications
8
117
2
4
Order By: Relevance
“…In congruence with our results, Clemente-Suarez et al ( 48 ) recently found little to no impact of confinement on the levels of anxiety of Olympic and Paralympic athletes. Authors attributed these phenomena to the larger experience of high-performance athletes in coping with competition-related anxiety and the higher cognitive resources professional athletes have.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In congruence with our results, Clemente-Suarez et al ( 48 ) recently found little to no impact of confinement on the levels of anxiety of Olympic and Paralympic athletes. Authors attributed these phenomena to the larger experience of high-performance athletes in coping with competition-related anxiety and the higher cognitive resources professional athletes have.…”
Section: Discussionsupporting
confidence: 93%
“…However, the same studies previously mentioned showed contradictory results in terms of academic levels and subjective perception of the confinement situation. On the one hand, chess players with university studies showed greater concern about the COVID-19 pandemic ( 49 ), while Olympic athletes with higher education showed more dissatisfaction with the confinement measures as a result of the COVID-19 pandemic ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in early evidence exploring the impact of COVID-19 lockdown in similar samples (di Fronso et al, 2020;Pillay et al, 2020). However, Clemente-Suárez et al (2020) reported no effects on Spanish Olympic athletes' mental health during the first month of confinement. The differences between studies are probably due to the diverse characteristics of the samples (i.e., as pointed by the authors, Olympic athletes are more used to cope with challenging situations) and to the number of days of confinement when participating in each study.…”
Section: Discussionsupporting
confidence: 85%
“…A study on perceived stress in Italian athletes showed that male athletes and elite athletes (i.e., competing at the national and/or international level) displayed lower perceived stress during the COVID-19 lockdown than female and non-elite athletes, respectively (di Fronso et al, 2020). Additionally, Clemente-Suárez et al (2020) found lower rates of anxiety in Olympic and Paralympic athletes than in the general population, suggesting that athletes may have more cognitive and emotional resources to face the confinement situation (Costa et al, 2020). Furthermore, in a qualitative study investigating psychological correlates of return to competition in basketball players, participants stated that participation in training programs prior to returning to sport increased their confidence in having better performance and lower fear of reinjury, and that reaching their pre-injury levels of performance was the main motivation to give "100% effort" in training programs before returning to competition (Conti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%